Rheological measurements for characterizing sticky point temperature of selected fruit powders: An experimental investigation. (February 2017) - Caparino, O.A.; Nindo, C.I.; Tang, J.; Sablani, S.S.
Abstract: Stickiness is one of the common problems frequently encountered during production, handling and storage of fruit powders with high concentration of low molecular weight sugars. Several techniques and devices were developed in the past to determine the level of stickiness of some of those products. Nevertheless, there is still a need for a simple, more accurate and reliable method. In this study, a new method to quantify and characterize the sticky point temperature ( T s ) of fruit powder was explored using a rheometer technique. The rheometer system utilized a serrated parallel plate to hold the samples and was operated in dynamic oscillation mode at a frequency of 1 Hz and a constant strain amplitude of 2%. The samples of a model fruit powder (Refractance Window (RW)-dried mango powder) were scanned from 25 to 95 °C at an increment of 10 °C and a holding time of 180 s for each increment. A crossover between the storage modulus ( G ′) and loss modulus ( G ″) was established and denoted as sticky point temperature of the model fruit powder. Results showed that the sticky point temperature obtained using the new method agreed well with the published data and can be considered as a suitable technique to characterize the sticky point temperature of sugar-rich materials. The procedure for sample conditioning and rheometric measurements to determine the sticky point temperature are straightforward. This new technique can measure the sticky point temperature of fruit powders with a high degree of repeatability and accuracy (SD = 0.58–1.73 °C). Highlights: Sticky point temperature of model sugar-rich fruit powder measured for the first time using a rheometer. The crossover of storage ( G ′) and loss ( G ″) modulus curves denotes sticky point temperature. Technique can potentially be used for rapid characterization of sugar rich food powder.